Study the Altman model for predicting the financial failure of companies by applying to ASE listed companies Une étude du modèle Altman pour prédire la défaillance financière des entreprises en les appliquant aux sociétés anonymes cotées à la bourse d’Amm - Medjdoub, Alaeddine; Guembour, Mohamed Amine (Finance and Business Economies Review, 2020)
This study aimed to measure the effectiveness of the credit model ((z-score) for predicting financial failure on the companies listed on the Amman Stock Exchange, and this model has been applied to 15 failed companies that were referred to liquidation or suspended companies and 15 continuous companies not referred to liquidation (sound). The study concluded that the Altman model was inclined to predict financial failure, and that it can be relied upon to judge the financial position of companies, but not by a large percentage.